Reengineering (Rekayasa Ulang) dan Penerapannya pada Institusi Pendidikan - Binti Nasukah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2019)
Today, globalization and rapidly technological advances demand educational institutions to adapt for survival. Technology, quality, effectiveness and efficiency demands, often requiring institutions to make changes, are not merely evolutionary but revolutionary. Consequently, various management, business concepts are adopted and applied with adjustments. One of them is known as re-engineering. Despite being an important topic in the early 90’s, reengineering is still rarely discussed in education. The article aims to present a discussion about the concept of reengineering, covering basic concepts, primarily in the difference with other management concepts, and its application to educational institutions–covering its component drivers ot the concept needs and the examples. Using literature study, it concludes that this concept is applicable to educational institutions, as the right tool for making institutional changes revolutionary. The concept can be applied in either support business (administrative process), or core business (process of teaching learning activities) to educational institutions. Reengineering conducted in the administrative process proved can bring up the new culture from the new system that has been built. While reengineering conducted in the teaching process proved can increase learner’s motivation and interest, due to the adoption of new methods in the process of teaching learning that involving technology.